2018
DOI: 10.1039/c8ra01913d
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of emamectin benzoate nanoformulations based on colloidal delivery systems and use in controlling Plutella xylostella (L.) (Lepidoptera: Plutellidae)

Abstract: Colloidal delivery systems have been widely used as carriers for controlled delivery of pesticides to improve the efficacy and photostability of natural and semi-synthetic pesticides. In this study, we have synthesized emamectin benzoate nanoformulations (EB + NFs) depending on polymeric nanocapsules (PNC) and two types of the nanosilica, mesoporous nanosilica (MCM-48) and silicon dioxide nanoparticles (SNPs) as carriers for the emamectin benzoate (EB). The fabricated nanoformulations were characterized by usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 44 publications
0
27
0
Order By: Relevance
“…Emamectin benzoate has been synthesized using polymeric nanocapsules (PNC) and two different nanosilica were used as the carrier. The study demonstrated that a maximum cumulative release of 51% was found in EB loaded with silicon dioxide nanoparticles (SNPs) [136]. This nanoformulations also protect some agrochemical compounds from photodegradation using the coating technique.…”
Section: Wo2017033153a1/2017 Oxadiazon Nanoemulsionsmentioning
confidence: 96%
“…Emamectin benzoate has been synthesized using polymeric nanocapsules (PNC) and two different nanosilica were used as the carrier. The study demonstrated that a maximum cumulative release of 51% was found in EB loaded with silicon dioxide nanoparticles (SNPs) [136]. This nanoformulations also protect some agrochemical compounds from photodegradation using the coating technique.…”
Section: Wo2017033153a1/2017 Oxadiazon Nanoemulsionsmentioning
confidence: 96%
“…Our results were in good agreement with Song et al [17], who found that the amount of chlorfenapyr-loaded on silica nanoparticles was 39.78% and that the chlorfenapyr might be physically adsorbed on the silica nanoparticles. Also, the SNPs illustrated a high loading ability for emamectin benzoate (87.5%) [18]. Consequently, these new nano-carriers such as CNCs and SNPs can be used to improve EMB insecticidal toxicity, solubility, and photodegradation and to overcome the disadvantages of EMB as mentioned earlier.…”
Section: Resultsmentioning
confidence: 99%
“…This is mainly because of their structural flexibility in forming nanomaterials of different sizes and shapes, low cost, large surface area, and non-toxicity and has also been approved by the U.S. Food and Drug Administration as a safe material [14,15,16]. Moreover, Silicon dioxide nanoparticles (SNPs) have been demonstrated to be capable of improving the dispersity, bioavailability, and efficiency of pesticide compounds and in overcoming the physiological resistance of pests [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…The surface chemical characteristics were studied by Fourier‐transform infrared (FTIR) spectrometry (Nicolet 6700, Thermo Fisher Scientific, Waltham, MA, USA). High‐performance liquid chromatography (HPLC) was measured (Agilent 1100, Agilent Technologies, Santa Clara, CA, USA), and the detection method followed the previous literature 37 …”
Section: Methodsmentioning
confidence: 99%
“…The injection volume was 20 μL with a flow rate of 1.0 mL min −1 , and the oven temperature was maintained at 30 °C. The detection wavelength was 245 nm 37 …”
Section: Methodsmentioning
confidence: 99%